Zinc Ameliorates the Osteogenic Effects of High Glucose in Vascular Smooth Muscle Cells - Laura A. Henze (MDPI AG, 2021)
In diabetic patients, medial vascular calcification is common and associated with increased cardiovascular mortality. Excessive glucose concentrations can activate the nuclear factor kappa-light-chain-enhancer of activated B-cells (NF-kB) and trigger pro-calcific effects in vascular smooth muscle cells (VSMCs), which may actively augment vascular calcification. Zinc is able to mitigate phosphate-induced VSMC calcification. Reduced serum zinc levels have been reported in diabetes mellitus. Therefore, in this study the effects of zinc supplementation were investigated in primary human aortic VSMCs exposed to excessive glucose concentrations. Zinc treatment was found to abrogate the stimulating effects of high glucose on VSMC calcification. Furthermore, zinc was found to blunt the increased expression of osteogenic and chondrogenic markers in high glucose-treated VSMCs. High glucose exposure was shown to activate NF-kB in VSMCs, an effect that was blunted by additional zinc treatment. Zinc was further found to increase the expression of TNFα-induced protein 3 (TNFAIP3) in high glucose-treated VSMCs. The silencing of TNFAIP3 was shown to abolish the protective effects of zinc on high glucose-induced NF-kB-dependent transcriptional activation, osteogenic marker expression, and the calcification of VSMCs. Silencing of the zinc-sensing receptor G protein-coupled receptor 39 (GPR39) was shown to abolish zinc-induced TNFAIP3 expression and the effects of zinc on high glucose-induced osteogenic marker expression. These observations indicate that zinc may be a protective factor during vascular calcification in hyperglycemic conditions.